Profiling of transcriptional regulators associated with starch biosynthesis in sorghum (Sorghum bicolor L.) - Xiao, Qianlin; Huang, Tianhui; Cao, Wan; Ma, Kuang; Liu, Tingting; Xing, Fangyu; Ma, Qiannan; Duan, Hong; Ling, Min; Ni, Xianlin; Liu, Zhizhai (Frontiers in Plant Science, 2022)
Starch presents as the major component of grain endosperm of sorghum (Sorghum bicolor L.) and other cereals, serving as the main energy supplier for both plants and animals, as well as important industrial raw materials of human beings, and was intensively concerned world widely. However, few documents focused on the pathway and transcriptional regulations of starch biosynthesis in sorghum. Here we presented the RNA-sequencing profiles of 20 sorghum tissues at different developmental stages to dissect key genes associated with sorghum starch biosynthesis and potential transcriptional regulations. A total of 1,708 highly expressed genes were detected, namely, 416 in grains, 736 in inflorescence, 73 in the stalk, 215 in the root, and 268 genes in the leaf. Besides, 27 genes encoded key enzymes associated with starch biosynthesis in sorghum were identified, namely, six for ADP-glucose pyrophosphorylase (AGPase), 10 for starch synthases (SSs), four for both starch-branching enzymes (SBE) and starch-debranching enzymes (DBEs), two for starch phosphorylases (SPs), and one for Brittle-1 (BT1). In addition, 65 transcription factors (TFs) that are highly expressed in endosperm were detected to co-express with 16 out of 27 genes, and 90 cis-elements were possessed by all 27 identified genes. Four NAC TFs were cloned, and the further assay results showed that three of them could in vitro bind to the CACGCAA motif within the promoters of SbBt1 and SbGBSSI, two key genes associated with starch biosynthesis in sorghum, functioning in similar ways that reported in other cereals. These results confirmed that sorghum starch biosynthesis might share the same or similar transcriptional regulations documented in other cereals, and provided informative references for further regulatory mechanism dissection of TFs involved in starch biosynthesis in sorghum.